2021
DOI: 10.1002/adma.202106865
|View full text |Cite
|
Sign up to set email alerts
|

Silk Embolic Material for Catheter‐Directed Endovascular Drug Delivery

Abstract: Embolization is a catheter‐based minimally invasive procedure that deliberately occludes diseased blood vessels for treatment purposes. A novel silk‐based embolic material (SEM) that is developed and optimized to provide tandem integration of both embolization and the delivery of therapeutics is reported. Natural silk is processed into fibroin proteins of varying lengths and is combined with charged nanoclay particles to allow visibility and injectability using clinical catheters as small as 600 μm in diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…The β-sheet structure helped to form the hydrogel network and payload efficiency was enhanced using the carbon nano tubes [37]. Air spun nanofibers for drug delivery [38], temperature-responsive poly (N-isopropylacrylamide) (PNIPAM) hydrogel and SF scaffold microcarriers for controlled and sustained drug release [39], silk based embolic material a potential next-generation multifunctional embolic agent including nivolumab labeled with albumin was delivered to treat vascular disorders, including malignancies, as well as achieve embolization [40]. Its utilization has been explored nevertheless in all possible directions for drug delivery.…”
Section: Silk Fibroinmentioning
confidence: 99%
“…The β-sheet structure helped to form the hydrogel network and payload efficiency was enhanced using the carbon nano tubes [37]. Air spun nanofibers for drug delivery [38], temperature-responsive poly (N-isopropylacrylamide) (PNIPAM) hydrogel and SF scaffold microcarriers for controlled and sustained drug release [39], silk based embolic material a potential next-generation multifunctional embolic agent including nivolumab labeled with albumin was delivered to treat vascular disorders, including malignancies, as well as achieve embolization [40]. Its utilization has been explored nevertheless in all possible directions for drug delivery.…”
Section: Silk Fibroinmentioning
confidence: 99%
“…On another front, regenerated silk fibroin (RSF), a naturally derived material, , can be potentially used as a stabilizing agent of salivary samples (Figure ). Unlike many protein-based biomaterials, RSF is inherently stable to moisture and changes in temperature thanks to its heterogeneous structure, which comprises hydrophobic domains and hydrophilic residues that generate protective microenvironments around labile molecules, including enzymes, antibodies, drugs, vaccines, cellular growth factors, genomic content (mechanisms of action of RSF summarized in Figure a). …”
Section: Potential Media and Techniques As Saliva Stabilizersmentioning
confidence: 99%
“…Furthermore, although not yet clinically approved, several efforts are being actively conducted to enable both real-time and postoperative imaging of biodegradable embolic agents. For example, several studies have shown that embolic agents loaded with radioopaque or magnetic-responsive materials are capable of real-time x-ray imaging, MRI, and CT imaging, as well as vessel embolization and biodegradation (32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%